The Achievement of Michael Wyschogrod - Soulen, R. Kendall (Modern theology, 2006)
Michael Wyschogrod is the most important Jewish thinker in the Modern Orthodox tradition since Joseph Soloveitchik. The key to Wyschogrod's significance consists in the point where he differs from Soloveitchik most dramatically. Whereas Soloveitchik held that "the religious or theological logos should not be employed as the medium of communication between two [different] faith communities", Wyschogrod regards such communication as a Jewish imperative. The essay explores Wyschogrod's use of "the theological logos as the medium of communication" with reference to his understanding of the relation of faith and reason as illustrated by the story of Franz Redner, a Holocaust survivor.